Conduction mechanisms, molecular modelling and micro-Raman studies of TlInSe2 chalcogenide crystal - Kalkan, Nevin; Celik, Sefa; Bas, Hanife; Ozel, Aysen E. (NATL INST OPTOELECTRONICS, 2017)
The temperature dependence of the electrical conductivity of the sample was studied for temperatures between 120 and 330 Kelvin. The DC measurements suggest that the electrical transport is governed by space charge limited conduction mechanism in the temperature range (210-330 K) and the related parameters, such as trap density, activation energy were calculated. The ac conductivity of the studied sample was investigated in the frequency range 10 Hz-20MHz and temperature range 173-373 K. The temperature dependence of both the ac conductivity and the frequency exponent, s is reasonably well interpreted in terms of the correlated barrier hopping model. Molecular Mechanics calculations with universal force field were performed on the TlIn(4)Se(1)s cluster that represent the local structure of the investigated crystal. The optimal geometries and the vibrational properties of the investigated cluster were calculated using universal force field method.
Keywords: Space charge limited conduction; ternary crystals; TlInSe2; micro-Raman spectroscopy; correlated barrier hopping; DIELECTRIC-PROPERTIES; AC CONDUCTIVITY; ELECTRICAL-CONDUCTIVITY; ELECTRONIC-STRUCTURE; OPTICAL-PROPERTIES; Materials Science; Optics; Physics